Zgodba nesrečne Lepe Vide v sodobni slovenski dramatiki - Terseglav, Marko (Traditiones (Ljubljana), 1999)
Lepa Vida (Fair Vida), a Slovene folk ballad, acquired its first literary echoand reinterpretation already in the 19th centuryč many have followed sincethen. The article analyzes dramatic texts about Lepa Vida, specifically three 20th century dramas. Even though ideas in each of them differ to a largeextent the author finds them most typical. The texts were written by Ivan Cankar, Rudi Šeligo and Matjaz Kmecl.
Keywords: slovenske ljudske legende; Lepa Vida; slovensko ljudsko slovstvo